STUDY OF MODIFIED PERFORATED BREAKWATER AS RENEWABLE ENERGY DEVICE - Oki Setyandito; Novandy Novandy; Nizam Nizam; Martin Anda; Riana Ayu Kusumadewi; Yureana Wijayanti (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2022)
Aim: This study investigates to determine the influence of wave steepness, relative freeboard, and breaker parameters on overtopping discharge at a perforated breakwater. Methodology and results: The research method used was using both a numerical model simulations on three-dimensional computational fluid dynamics (CFD) modelling software namely FLOW-3D; and empirical equation computation. The evaluation of both approaches were performed for understanding the characteristics of wave discharge that overtopping the perforated breakwater. The experimental results of modified perforated breakwater revealed that the lowest slope possible with the highest porosity possible can generate the highest value of dimensionless overtopping discharge for wave energy harvesting. Conclusion, significance and impact study: The findings of this study formulated the optimum slope and porosity to the highest wave energy harvested. Further studies recommend that data collection from onsite trials of modified perforated breakwater are performed.